2005
DOI: 10.1140/epjd/e2005-00208-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutually unbiased phase states, phase uncertainties, and Gauss sums

Abstract: Mutually unbiased bases (MUBs), which are such that the inner product between two vectors in different orthogonal bases is a constant equal to 1/ 2). Quantum Fourier transforms of the components in vectors of the bases define a more general class of MUBs with multiplicative characters and additive ones altogether. We investigate the complementary properties of the above phase operator with respect to the number operator. We also study the phase probability distribution and variance for general pure quantum ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 26 publications
1
48
0
3
Order By: Relevance
“…This concept plays a key role in a search for a rigorous formulation of quantum complementarity and lends itself to numerous applications in quantum information theory. It is a well-known fact (see, e.g., [1]- [9] and references therein) that H q supports at most q + 1 pairwise mutually unbiased bases (MUBs) and various algebraic geometrical constructions of such q + 1, or complete, sets of MUBs have been found when q = p r , with p being a prime and r a positive integer. In our recent paper [10] we have demonstrated that the bases of such a set can be viewed as points of a proper conic (or, more generally, of an oval) in a projective plane of order q.…”
mentioning
confidence: 99%
“…This concept plays a key role in a search for a rigorous formulation of quantum complementarity and lends itself to numerous applications in quantum information theory. It is a well-known fact (see, e.g., [1]- [9] and references therein) that H q supports at most q + 1 pairwise mutually unbiased bases (MUBs) and various algebraic geometrical constructions of such q + 1, or complete, sets of MUBs have been found when q = p r , with p being a prime and r a positive integer. In our recent paper [10] we have demonstrated that the bases of such a set can be viewed as points of a proper conic (or, more generally, of an oval) in a projective plane of order q.…”
mentioning
confidence: 99%
“…Different explicit constructions of MUBs in prime power dimensions have been suggested in a number of recent papers [49][50][51][52][53][54][55]. We follow here the approach established in Refs.…”
Section: Mutually Unbiased Bases: Basic Backgroundmentioning
confidence: 99%
“…As shown in Ref [44], the only MUB structure for a two-qutrit system is (4,6), where 4 is the number of the separable bases and 6 is the number of the bipartite entangled bases. However in three-qutrit case, there are five sets of MUBs with different structures, namely {(0, 12, 16), (1,9,18), (2,6,20), (3,3,22), (4,0,24)} [21,44]. It is easy to see that the (0, 12, 16) set of MUBs has the minimum physical complexity.…”
Section: The Physical Complexity For Implementing the Mums In The mentioning
confidence: 99%